RELATIONS OF RUSSIAN AND UZBEK LITERATURE IN OYBEK’S WORK - Yuldasheva Laylo Ulugbekovna (European Journal of Humanities and Educational Advancements, 2022)
Oybek is widely known as a wonderful writer and a soulful poet, but relatively little is known to the reader as a critic and literary critic. In this article highlights of relations of Russian and Uzbek literature in Oybek’s work.